2010
DOI: 10.1063/1.3496482
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram of self-assembled rigid rods on two-dimensional lattices: Theory and Monte Carlo simulations

Abstract: Monte Carlo simulations and finite-size scaling analysis have been carried out to study the critical behavior in a two-dimensional system of particles with two bonding sites that, by decreasing temperature or increasing density, polymerize reversibly into chains with discrete orientational degrees of freedom and, at the same time, undergo a continuous isotropic-nematic (IN) transition. A complete phase diagram was obtained as a function of temperature and density. The numerical results were compared with Mean … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 57 publications
5
47
0
Order By: Relevance
“…Rod-like particles [11,12] like spherocylinders, spheroids, and ellipsoids are the most simple anisotropic colloidal particles. They are convex and apolar and of big importance since they may evolve the industrially important nematic phase and serve as excellent model systems for most liquid crystals [13][14][15]. A further member of convex and apolar particles are the platelets [16][17][18][19][20].…”
Section: Geometric Classification Of Colloidal Particlesmentioning
confidence: 99%
“…Rod-like particles [11,12] like spherocylinders, spheroids, and ellipsoids are the most simple anisotropic colloidal particles. They are convex and apolar and of big importance since they may evolve the industrially important nematic phase and serve as excellent model systems for most liquid crystals [13][14][15]. A further member of convex and apolar particles are the platelets [16][17][18][19][20].…”
Section: Geometric Classification Of Colloidal Particlesmentioning
confidence: 99%
“…6); and (d) a logarithmic decrease with θ of the critical curve when θ → 0, in agreement with other analytical approach. 9 In an earlier study, 22 in which the critical behavior of SARRs on the square lattice was addressed, it was shown that in the full coverage case (θ = 1.0), the Hamiltonian of the SARRs model maps exactly onto the Ising model one (q = 2 Potts model) with coupling constant w I sing = w SARRs /4. In contrast, the 2D SARRs model on the triangular lattice cannot be mapped on q = 3 Potts model, as can be easily seen from Eq.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 3 shows the critical line reported in Ref. 22 and only one point (the lowest coverage obtained) of the critical line reported in Ref. 16.…”
Section: Phase Diagrams Of Sarrs On Square Triangular and Honeycombmentioning
confidence: 99%
See 2 more Smart Citations